English Teacher’s Perseption The Words Curiculum Merdeka Belajar Implementation In Different Levels Education - Elnardus Fransiskus Jafrinus Namo (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Indonesia's educational system is currently undergoing a significant transformation with the introduction of the